The Impact of Social Media Activities on ‘Labubu the Monsters' Brand Awareness and Brand Image - Sadihin, Grace Javiera; Angelika, Patricia Evelyn; Wardana Putra, I Ketut Rangga; Aryaputra, Fari Agil; Otniel, Theodorus (ASEAN Marketing Journal, 2025)
This study aims to investigate the impact of social media activities on brand image and brand awareness. A quantitative study was conducted using a validated questionnaire distributed to a sample of 348 respondents of Gen Z, Gen Y, and Gen X who use social media and are familiar with Labubu The Monsters. Multiple regression analysis was performed using SPSS version 27 to test the hypotheses. The results revealed a significant impact of social media activities on brand awareness and brand image. It was found that entertainment, trendiness, and influencers affect brand awareness, while entertainment, EWOM, trendiness, and influencers affect brand image. This study is one of the few to examine the impact of social media activities on brand awareness and brand image for Labubu The Monsters toys in Indonesia. The study provides several theoretical and practical implications that can benefit Labubu The Monsters’ managers in their marketing efforts through various social media activities.